Depicting Role and Power on EFL Teacher’s Lesson Plan: Critical Discourse Analysis (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
Instructional process requires a good lesson plan which draws a number of mutual activities between students and teacher. However, the lesson plan is designed not to direct the students to be more autonomous during the process or to implement the student-centered learning. Therefore, this study is initiated to analyse the role and power depicted on the lesson plan which is taken from the seventh grade’s teacher. This study is closely related to critical discourse analysis which employs theory of ‘Role and Power’ by Brooks (2015). The lesson plans’ evaluation is indicated that the teacher dominantly plays the role during the instructional process. On one hand, she has more power in performing her roles as teaching manager, guide, and facilitator. For example: based on the lesson plan, the teacher has dominant role in directing as well as questioning the students in the teaching and learning process as the teachers’ dominance which was depicted on the lesson plans. In this context, the teacher characterizes themselves as the dominant figures to perform their duties in the instructional process.